Interactive technology and human–animal encounters at the zoo. Issue 98 (February 2017) - Webber, Sarah; Carter, Marcus; Smith, Wally; Vetere, Frank
Abstract: In this paper we investigate social dimensions of technology use in human–animal interactions, through a study of interactive systems at the zoo. Zoos are a familiar place for encounters between humans and non-domesticated animals. Accordingly, we examine zoos as a significant site to extend research into animal–computer interaction (ACI). We present a case study that examines the deployment and use of new digital technologies that intervene in, and influence, human–animal relationships. The paper reports on interactive systems in use at Melbourne Zoo. The study investigates the use and impact of technology in the course of human–animal encounters, including how human use of technology in this setting shapes encounters in subtle ways. We examine five interactive systems used by visitors ( Digital Signs and the Zoopermarket ), by zoo personnel with visitors ( Educator Screens and Volunteer iPads ), and by zoo personnel with animals ( Apps for Apes ). Our work draws broad insights for the design and understanding of animal–human–computer interaction at the zoo, as a catalyst for further research into this site of considerable significance to animal-computer interaction. We identified four key themes in the ways that interactive systems are intervening in human–animal encounters at the zoo. Firstly, interactive technology at the zoo risks distracting from visitors' encounters with animals. Secondly, the appearance and use of technology moreover runs counter to expectations of naturalistic zoo landscapes. Thirdly, interactive systems however offer opportunities to enhance important aspects of visitors' experience of animal encounters, and to widen the temporal and spatial dimensions of the encounter. Finally, we interpret these insights by examining how technology is used in the context of interactions between numerous human and animal actors, and in a setting impacted by complex social and organisational forces. From this, we identify the need for ACI to consider technology use by diverse people and animals; that multiple interactions may occur at once; the diverse social activities that may surround human–animal interactions; the distributed form of interactions between multiple participants; and the performative nature of some human–animal encounters. Highlights: Zoos offer a site to study technology as part of complex human–animal interactions. Technology shapes human–animal encounters in subtle ways. Design needs to accommodate diverse human and animal participants. Human–animal interactions may be distributed or entail multiple interactions. Interactions occur as part of social activities and can involve performance.